2003
DOI: 10.1093/brain/awg079
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning elicited by voluntary drive

Abstract: Motor training consisting of voluntary movements leads to performance improvements and results in characteristic reorganizational changes in the motor cortex. It has been proposed that repetition of passively elicited movements could also lead to improvements in motor performance. In this study, we compared behavioural gains, changes in functional MRI (fMRI) activation in the contralateral primary motor cortex (cM1) and in motor cortex excitability measured with transcranial magnetic stimulation (TMS) after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
376
2
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(418 citation statements)
references
References 31 publications
34
376
2
6
Order By: Relevance
“…Previous studies showed in accordance with these ideas that the brain networks subserving passive movement and overt execution overlap strongly (Carel et al, 2000;Puce et al, 1995;Weiller et al, 1996;Yetkin et al, 1995) (but see Mima et al, 1999). Again, evidence suggests that passive movement can be successfully applied in motor rehabilitation (Dechaumont-Palacin et al, 2008;Hesse et al, 1995;Lewis and Byblow, 2004;Lindberg et al, 2004;Ward et al, 2006) (but see Lotze et al, 2003). Because the overt movement of the limb in passive movement is not controlled by the participant, we consider the passive movement condition used in the present manuscript as a covert movement mode as well.…”
Section: Introductionmentioning
confidence: 60%
“…Previous studies showed in accordance with these ideas that the brain networks subserving passive movement and overt execution overlap strongly (Carel et al, 2000;Puce et al, 1995;Weiller et al, 1996;Yetkin et al, 1995) (but see Mima et al, 1999). Again, evidence suggests that passive movement can be successfully applied in motor rehabilitation (Dechaumont-Palacin et al, 2008;Hesse et al, 1995;Lewis and Byblow, 2004;Lindberg et al, 2004;Ward et al, 2006) (but see Lotze et al, 2003). Because the overt movement of the limb in passive movement is not controlled by the participant, we consider the passive movement condition used in the present manuscript as a covert movement mode as well.…”
Section: Introductionmentioning
confidence: 60%
“…9 During active training, subjects were instructed to perform voluntary wrist flexion-extension movements of a specified duration in an articulated splint. Therefore, voluntary movements falling within a specified time window displayed on the screen monitor were considered correct hits.…”
Section: Role Of Volition In Motor Learningmentioning
confidence: 99%
“…internally mediated and externally guided or mediated movements (Lotze, Braun, Birbaumer, Anders, & Cohen, 2003). Behavioural reactions to external stimuli are usually less impaired than internally initiated intentional behavioural actions (Romo & Schultz, 1992).…”
Section: Studies Of Brain Activation Patterns Show Clear Functional Dmentioning
confidence: 99%